PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PENCURIAN DENGAN KEKERASAN SECARA BERSAMA-SAMA - Kelvin Leo Putra; Azmi Syah Putra (Reformasi Hukum Trisakti, 2022)
The stealing offense is a group offence. People must be more cautious due to the increase in theft-related criminal cases in Indonesia. In DKI Jakarta, there were 1,279 cases of theft without violence in 2019 and 266 cases of theft with violence, according to research by the Central Statistics Agency. In 2020, there was an increase in cases of theft without violence, reaching 1,950 cases, and a decrease in cases of theft with violence, reaching 184 cases. The formulation of the issue is how the judge should apply Article 368 Paragraph 1 and Article 55 Paragraph 1 of the Criminal Code given the facts and components of the defendant's activities. The nature of normative legal study, its analytical descriptive, and the data analysis is qualitative, in the research. How to use deductive reasoning to arrive to conclusions. Results of the study, discussion, and conclusions The defendant should have been punished under Article 365 Paragraph 1 Jo Paragraph 2 to 1 and 2 of the Criminal Code, which deals with theft that is preceded by threats of violence to facilitate theft, committed on a public highway, and committed jointly, i.e. by two people or more.